The Very Quiet Cricket - Carle, Eric. (New York : Philomel Books, 1990)
A very quiet cricket who wants to rub his wings together and make a sound as do so many other animals finally achieves his wish. The cricket's sound is reproduced at the end of the book.
Horn Book
Keywords: Crickets -- Fiction; Crickets -- Fiction; Animal sounds -- Fiction; Toy and movable books; Animal communication -- Fiction; Toy and movable books